Odpowiedzi

Najlepsza Odpowiedź!
2009-11-26T19:34:12+01:00
3/5 +(1- 1/10 ) :( 4/5 +1)=
3/5 + 9/10 : 1 4/5=
3/5 + 9/10 * 9/10=
3/5 + 81/100 =
60/100 + 81/100=
141/100 = 1 41/100


1/6 +1- 3/4 : (5/3 - 1/2) =
1 1/6 - 3/4 : (10/6 - 3/6) =
1 1/6 - 3/4 : 7/6 =
1 1/6 - 3/4 * 6/7 =
1 1/6 - 9/14=
7/6 - 9/14 =
49/42 - 27/42=
22/42

4/9 * ( 1/3 - 1/6 ) : 1/9 =
4/9 * (2/6 - 1/6) :1/9=
4/9 * 1/6 : 1/9=
2/27 : 1/9=
2/27 * 9/1=
2/3

1 5 1
2009-11-26T19:35:48+01:00
1) 3/5 +(1- 1/10 ) :( 4/5 +1)= 3/5 + 9/10 : 1 4/5=3/5 + 9/10 : 14/5= 3/5 + 9/10 x 5/14 = 3/5 + 45/50 = 30/50 + 45/50 = 75/50 = 1 25/50= 1 1/2

2) 1/6 +1- 3/4 : (5/3 - 1/2) = 1 1/6 + 3/4 : ( 10/ 6 - 3/6)= 1 1/6 - 3/4 : (-7/6) = 1 1/6 - 3/4 x (-6/7) = 1 1/6 - (-18/28) = 7/6 + 18/28 = 98/84 + 54/84= 152/84 = 1 68/84 = 1 34/42= 1 17/21

3) 4/9 x ( 1/3 - 1/6 ) : 1/9 = 4/9 x (2/6 - 1/6) : 1/9= 4/9 x 1/6 : 1/9= 4/54: 1/9= 4/54 x 9/1= 27/54 = 3/6 = 1/2



x to jest pomnożyć

1 5 1